The transcriptional landscape and small RNAs in Acinetobacter baumannii AB5075 during antibiotic and environmental stress. - Bakheet, Ali Ahmad (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2024)
Multi-drug resistant Acinetobacter baumannii is considered a major challenge because it causes a variety of serious infections. Studying these bacteria at the level of their genetic response could facilitate finding a way to treat them. Tracking gene expression throughout the growth phases or when affected by any environmental stresses can deepen our understanding of how genes work and how cells function. Here, we studied global gene expression of A. baumannii AB5075 using RNA-seq under the influence of 12 different stresses divided into three groups. The first group includes five growth stages in rich medium, the second group includes four environmental shocks (osmotic, iron limitation and two antibiotic shocks), and the third group contains temperatures shift experiments (between 22C and 37C). An important finding is the dramatic up-regulation of the phenyl-acetic acid (paa) pathway including paaA, paaB, paaC, paaJ, paaK and paaZ in late exponential and early stationary phase in rich medium which influences virulence, antibiotic resistance, and biofilm formation. In the environmental shock conditions, we reveal that the transcriptional responses were similar between osmotic shock and iron limiting conditions, and the effect of antibiotics (exposure to chloramphenicol and tetracycline), respectively, indicating that similar pathways are involved in these stress responses. These included genes encoding siderophore Acinetobactin encoding genes that were up-regulated in both osmotic shock and iron limiting conditions. The two antibiotic shocks showed gene expression changes to a much larger than osmotic shock and iron limiting conditions suggesting that protein synthesis stress require a much larger transcriptomic response to cope with the stress compared to the osmotic and iron limitation stress. A response to the antibiotic stress was observed to be a down-regulation of the NADH-quinone oxidoreductase complex, a central protein complex in the respiratory chain, indicating the antibiotics could influence the proton gradient across the membrane or that further growth and ATP synthesis should be immediately stopped. When growing at different temperatures, there were large changes to the transcriptome in all temperature comparisons. The virulence-associated otsAB operon and paa genes were strongly up-regulated upon temperature shift. Type IV pilus encoding genes were down-regulated genes when cells were experiencing a temperature upshift (TS) which could mean that DNA uptake is at least transiently down-regulated when A. baumannii enters a warm-blooded host. In contrast, a temperature downshift induced expression of the Type 6 Secretion System and Csu pili. We also provide a first expression landscape of sRNAs in the suite of 12 conditions. We observed dynamic expression of many small RNAs across the 12 conditions. The sRNAs sRNA99 and sRNA100 very quickly dropped in abundance when the cells experienced antibiotic shocks which was independently validated by Northern blotting for sRNA99 and sRNA100. Deletion of sRNA99 and sRNA100, resulted in large expression changes in MEP in the mutants compared to the WT, which will require further analysis. The sRNA44 was investigated mechanistically in more detail in this study because previous data in A. baumannii AB5075 suggested that sRNA44 was ligated to the mRNA of the biofilm-associated bap gene. We show that sRNA44 translationally represses bap translation in E. coli and that overexpression of sRNA44 reduces bap mRNA levels, likely induced by a base-pairing mechanism. Deletion of sRNA44 and bap showed that bap is required for full biofilm formation after 24h, while deletion of sRNA44 increased biofilm formation suggesting that sRNA44 is a regulator of A. baumannii biofilm formation.
APPROVED
Keywords: Small RNA; Stress responses; Antibiotic responses; Transcriptome; Acinetobacter